Comparative genomics of multi-drug resistant Escherichia coli ST131 from human, animal, and environmental sources in the Czech Republic - Michaela Ruzickova; Ivana Karola; Tomas Nohejl; Iva Sukkar; Jana Palkovicova; Ivo Papousek; Max L. Cummins; Steven P. Djordjevic; Monika Dolejska (Ecotoxicology and Environmental Safety)
Globally, Escherichia coli is a leading cause of multiple drug-resistant (MDR) extraintestinal infections. ST131 is an MDR, pandemic sequence type that causes urinary tract and bloodstream infections in humans and companion animals, and systemic infections affecting multiple organs in poultry. ST131 has also been isolated from wastewater treatment plants and diverse wildlife sources. Studies investigating the phylogeny of ST131 from a One Health perspective are, however, limited. We performed whole-genome sequencing on 898 ST131 isolates from humans (n = 713), diverse environments (n = 139), wildlife (n = 32), food animals (n = 13), and companion animals (n = 1), sourced from the Czech Republic from 2005–2021, to identify evidence of clonal spread across different sources and to investigate carriage of genes encoding extended-spectrum beta-lactamases (ESBLs). ST131 belonging to clades C1 (262/898; 29 %) and C2 (528/898; 58.8 %) were dominant in our study. Irrespective of source or clade designation, most isolates (72.4 %) carried a blaCTX-M allele, with those residing in clade C1 carrying blaCTX-M-27, while those in clade C2 carried blaCTX-M-15. IncF plasmid sequence types were also segregated by clades, with F29:A-:B10 residing in clade A, F1:A2:B20 in clade C1, and F2:A1:B- and F31/F36:A4:B1 partitioning to clade C2. Clonal ST131 isolates (0–10 single-nucleotide polymorphisms; SNPs) were identified from humans, wild birds, and wastewater. In summary, our study showed that clonal ST131 isolates can be recovered across diverse sources in the Czech Republic, underscoring the importance of studying pandemic ExPEC lineages within a One Health context and across widespread geographic locations.